2012
DOI: 10.3109/14767058.2012.705396
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidant generation in the metabolism of hypoxanthine to uric acid and endothelial dysfunction in early-onset and late-onset preeclamptic women

Abstract: We found that increased oxidant generation during metabolism of hypoxanthine to uric acid may impair endothelial function in early-onset preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…FMD was significantly lower in women with less severe forms of preeclampsia 31, 34, 36, 37, 39 compared to women who had normotensive pregnancies (SMD: −0.95, 95% CI: −1.30, −0.59, p<0.001, Figure S2, Panel A). Similar results were observed in studies examining women with more severe forms of preeclampsia 31, 34, 36, 39 compared to women who had normotensive pregnancies (SMD: −1.74, 95% CI: −2.65, −0.83, p<0.001, Figure S2, Panel B).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…FMD was significantly lower in women with less severe forms of preeclampsia 31, 34, 36, 37, 39 compared to women who had normotensive pregnancies (SMD: −0.95, 95% CI: −1.30, −0.59, p<0.001, Figure S2, Panel A). Similar results were observed in studies examining women with more severe forms of preeclampsia 31, 34, 36, 39 compared to women who had normotensive pregnancies (SMD: −1.74, 95% CI: −2.65, −0.83, p<0.001, Figure S2, Panel B).…”
Section: Resultsmentioning
confidence: 98%
“…Excluding one study that observed a very large effect 33 resulted in a slight reduction in the SMD (−1.20, 95% CI: −1.70, −0.70, p<0.001) and heterogeneity (Q=80.6, p<0.001, I 2 =86%). The magnitude of the overall effect was attenuated in sensitivity analyses of studies that excluded smokers (SMD: −1.30, 95% CI:−1.94, −0.66, p<0.001), 23, 30, 32, 3436, 3941 women with chronic hypertension (SMD: −1.15, 95% CI: −1.64, −0.66, p<0.001) 3032, 3640 or both (SMD: −1.30, 95% CI:−2.05, −0.55, p<0.001). 30, 32, 36, 39, 40 Selecting different time points for one study that included multiple time points 23 did not alter the results.…”
Section: Resultsmentioning
confidence: 98%
“…We found that FMD in patients with early-onset preeclampsia was significantly lower than in those with late-onset preeclampsia. 16 This indicates that endothelial dysfunction is more severe in early-onset preeclampsia than in late-onset preeclampsia. Given that FMD was not tracked long term after delivery in the present study, further studies will be needed to address this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 We previously found that FMD of the brachial artery, a known marker of vascular endothelial function, is decreased in preeclamptic women. 15,16 Pre-existing chronic hypertension, obesity, diabetes mellitus and systemic lupus erythematosus may initiate vasospasms secondary to endothelial dysfunction, and endothelial dysfunction does not completely improve after delivery. Pregnancies in patients with these pre-existing conditions have a greater risk of preeclampsia, which frequently becomes apparent during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Γνωρίζοντας ότι οι γυναίκες με ιστορικό ΠΕΚ έχουν αυξημένο καρδιαγγειακό κίνδυνο251,252 , είναι λογικό να αναμένει κανείς την αύξηση της ΤΣΚ σε αυτό τον πληθυσμό. Πράγματι, περιγράφεται αύξηση του c-f PWV σε γυναίκες με ΠΕΚ, όχι μόνο σε σχέση με τις νορμοτασικές εγκύους Το ουρικό οξύ, το οποίο είναι σήμερα γνωστό ότι αυξάνει στην ΠΕΚ όχι μόνο λόγω μειωμένης κάθαρσης, αλλά και λόγω αυξημένης καταστροφής τροφοβλαστικών κυττάρων και ισχαιμίας, προάγει την συστηματική φλεγμονή314 , καθώς και την οξείδωση και την ενδοθηλιακή δυσλειτουργία315 . Οι συνθήκες αυτές με την σειρά τους, ευοδώνουν την αρτηριακή σκλήρυνση και κατά συνέπεια συμβάλλουν στην αύξηση της ΤΣΚ.Φαίνεται λοιπόν, ότι οι παράγοντες κινδύνου για καρδιαγγειακή νόσο ασκούν επίδραση στην σκλήρυνση των αγγείων τόσο στο γενικό πληθυσμό, όσο και στην κύηση.Στη μελέτη μας δεν βρέθηκε διαφορά επίπτωσης της ΠΕΚ σε σχέση με το κάπνισμα (38% ποσοστό καπνιστριών και στις δύο ομάδες).…”
unclassified